Evaluation of Jordanian Banks Websites Usability - Rafi’i Al Abdulraheem, Abeer; Abumalloh, Rabab; Abu-Ulbeh, Waheeb (International Journal of Engineering and Technology, 2018)
Being convinced of the importance of online banking, as a new competitive advantage that every bank around the world is rushing to gain, the following research question motivated the authors to investigate; to what extent is any bank’s website is usable and beneficial to customers? This research is about evaluating Jordanian banks’ websites; we have followed one approach for evaluating these websites. This approach is evaluating our sample according to the WEBUSE model developed by Chiew and Salim (2003). The results of the evaluation process have indicated that the banks websites are nearly of close quality in their functional attributes or services the bank’s website offers, as well as in the user’s acceptance of other features adopted in the WEBUSE index. Finally, this research concludes that the chosen sample of Jordanian banks’ websites are of excellent to good quality or usability level.